Competency-Based Approach in Higher Education and Prospects for The Development of The Uzbek Language - Jurayeva Turgunoy Umarjonovna (Scientific Trends, 2024)
This article analyzes theoretical and practical aspects of a competency-based approach in higher education. The essence of the concept of competence, its application in the educational process and its role in the formation of pedagogical skills are covered. Also, within the framework of the modernization of the higher education system, current issues of the development of professional qualifications and competencies, innovative approaches based on global and national experiences have been proposed. The prospects for the introduction of a competency model in the reforms of the educational system of Uzbekistan are considered.
Keywords: competence, higher education, continuing education, professional qualification, pedagogical skills, innovative education, modernization of the educational system, knowledge, qualifications and skills, educational system, competitive personnel, methodological methods, qualified specialist.